The relationship between coping strategies and infertility self-efficacy with pregnancy outcomes of women undergoing in vitro fertilization: A prospective cohort study - Hosna Mirzaasgari; Fereshte Momeni; Abbas Pourshahbaz; Farahnaz Keshavarzi; Masoud Hatami (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Assisted reproductive technology treatments are stressful procedures, but there are individual differences in the emotional response to them. Differences in response to this stress may be related to the outcome of infertility treatment. Objective: This study aimed to investigate the relationship between coping strategies and infertility self-efficacy with pregnancy outcomes of women undergoing in vitro fertilization/intracytoplasmic sperm injection treatment. Materials and Methods: This was a prospective cohort study and the 154 infertile women were psychologically evaluated in 2 stages: once before ovarian stimulation and again during embryo transfer. The research measurements used were the Revised COPE, the Depression Anxiety Stress Scale (DASS-21) and the Infertility Self-Efficacy Scale. Results: There was no significant difference between the group of non-pregnant women and the positive pregnancy group in terms of coping strategies (mental rumination, self-blame, active confronting, goal replacement, avoidance) or self-efficacy in either of the 2 stages of ovarian stimulation and embryo transfer. The Mann-Whitney test did not show any statistical difference between the clinically pregnant women and the only laboratory positive pregnant group. Moreover, the self-blame and mental rumination strategies were positively related with anxiety and depression. Conversely, active confronting, goal replacement, avoidance and self-efficacy were associated with decreased depression, anxiety and stress levels. Conclusion: It can be concluded that there is no relationship between coping strategies and infertility self-efficacy with in vitro fertilization/intracytoplasmic sperm injection outcomes. Further research is needed to clarify the effects of other psychological factors on the pregnancy outcomes of assisted reproductive treatment.